"At Least We Could Give Our Input": Underrepresented Student Narratives on Conventional and Guided Inquiry-Based Laboratory Approaches. (22nd March 2021) - Hernandez, Tess; Donnelly-Hermosillo, Dermot F; Person, Eric; Hansen, Alexandria K
Synopsis: Policy documents continually stress the need to develop a scientifically literate and diverse workforce. One commonly recommended way to achieve these goals is through the redesign of introductory level science courses to foster students' interest in science. Such redesigns take advantage of a myriad of evidence-based strategies such as inquiry and context-based approaches that place students at the center of learning. In this study, we report on interviews of 10 female students participating in a zoo-context guided-inquiry laboratory structure within an introductory chemistry course. Half of these students were taking the laboratory for the first time (first-experience, n = 5), and half were taking the laboratory a second time (second-experience; n = 5), having failed the course in a conventional format a previous semester. The conventional laboratory format was designed to reinforce lecture content with prescriptive-style laboratories while the zoo-based guided-inquiry laboratory structure was focused on supporting student-designed investigations tied to zoo exhibits. Using interviews, we sought to understand students' experiences and how such experiences could inform future laboratory iterations. Through inductive thematic analysis, we found three themes describing student experiences in both laboratory environments—classroom relationships, relevancy of the work, and ownership of the experiments. This work describes the nuances across student perspectives of laboratory approaches and the implications of these findings for iterations to laboratory structures toward greater student science interest, both for conventional and guided-inquiry approaches.